Teachers' Perceptions of Coexistence in Their Educational Centres - Díaz Pino, Alejandra Alexia; González Córcoles, María del Rosario; García de Rivera Hurtado, Marian; Pérez González, Lourdes (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2019)
This paper deals with one of the research lines on coexistence carried out by the group PREVyCON in collaboration with CES Don Bosco College. More specifically, it focuses on the HELP Project, a pedagogical proposal for the improvement of coexistence and school atmosphere. The promotion of a positive coexistence in school requires teachers who are genuinely willing to work on it. However, their training might be sometimes greatly limited by their perceptions about the key components of coexistence. Consequently, it seems to be necessary to carry out projects like the one presented here, in order to identify the ideas of in-service teachers and analyse to what extent can these perceptions facilitate or hinder coexistence. Thus the main objective of this descriptive research study is to identify and discuss teacher's ideas on the role of coexistence in their educational centres. The results reveal that 1-the professional atmosphere is one of the most valued aspects, 2- the conflict should be avoided, 3-there is a need to promote the development of socio-emotional skills both on students and teachers, 4-the urgency to rely on moments to set clear coexistence rules and make proposals for improvement.
Keywords: coexistence; teachers; Primary Education